Tyzzeria parvula (Kotlan, 1933) Klimes, 1963 (Apicomplexa: Eimeriidae) in the greylag goose (Anser anser Linnaeus, 1758) in southeastern Brazil - Bruno P. Berto (Revista Brasileira de Parasitologia Veterinária, 2007)
Tyzzeria parvula from the greylag goose (Anser anser) is described in Southeastern Brazil. Oocysts are spherical to subspherical ranging from 12.4-180 to 10.7-15.9µm (15.4 X 13.4 µm), shape index 1.15, with a double layered wall 0.4 to 0.7 µm thick (n=20), outer smooth and colorless, inner pale greenish. Micropyle is absent, but oocyst residuum is present containing numerous granules and spherules. Surrounded by residuum there are eight sporozoites having one end round and other fine and slightly curved.